PENGUATAN KAPASITAS ORGANISASI NON-PROFIT MELALUI IMPLEMENTASI SISTEM MANAJEMEN PROYEK BERBASIS ARIMA - Ahmad Jet Alamin A; Adrian K. Tarigan; Nurul Suci Anggraeni Nasution (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This PkM activity aims to strengthen the capacity of non-profit organizations in program planning and control through the implementation of a Project Management System (SMP) equipped with ARIMA-based forecasting features. Partner issues include activity planning that is not yet data-based, fluctuations in donations/service requests that are difficult to predict, unstable volunteer scheduling, and inconsistent achievement reporting. Interventions are carried out through needs assessments, strengthening project governance (SOP, RACI, logframe, M&E), development of data templates and dashboards, and training and mentoring on the application of ARIMA to predict key indicators (e.g., monthly donations, number of beneficiaries, need for aid packages). Success is measured by increasing project administration compliance, planning accuracy (reduced forecasting errors), and increasing the timeliness of reporting and the use of dashboards in decision-making meetings.